2019
DOI: 10.9734/cjast/2019/v33i230053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sulphur Sources and Levels on Growth, Yield and Quality of Onion (Allium cepa L.)

Abstract: A field experiment was conducted during rabi season at Trihut college of Agriculture Dholi, Muzaffarpur to evaluate the response of sources (Elemental sulphur and gypsum) and different doses (15, 30 and 45 kg S ha-1) of sulphur growth yield and quality of onion. Bulb yield, nutrient content in onion and nutrient uptake were significantly improved by the application of sulphur by gypsum over elenmental sulphur. Amongst sulphur doses, the application of sulphur at 40 kg/ha showed significant superiority over oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 1 publication
2
3
0
Order By: Relevance
“…Nitrogen application at 150 kg N ha -1 resulted in higher yield than other levels tested. Similar results have been reported by Diaz-Perez et al (2003); Singh et al (2004); Zaman et al (2011); Alassaf (2013). Influence of plant spacing with respect to average weight of bulb was AWB: Average weight of bulb (g); DB: Diameter of bulb (cm); YBP: Yield of bulb plot -1 (kg); YBH: Yield of bulb ha -1 (q); TSS: Total soluble solid found significant variation.…”
Section: Resultssupporting
confidence: 91%
“…Nitrogen application at 150 kg N ha -1 resulted in higher yield than other levels tested. Similar results have been reported by Diaz-Perez et al (2003); Singh et al (2004); Zaman et al (2011); Alassaf (2013). Influence of plant spacing with respect to average weight of bulb was AWB: Average weight of bulb (g); DB: Diameter of bulb (cm); YBP: Yield of bulb plot -1 (kg); YBH: Yield of bulb ha -1 (q); TSS: Total soluble solid found significant variation.…”
Section: Resultssupporting
confidence: 91%
“…plant height both at 60 and 90 DAS (31.88 and 49.05 cm), number of leaves per plant both at 60 and 90 DAS (5.22 and 6.60), and chlorophyll content at 60 DAS (31.88 mg/g in leaves) were recorded under control, respectively which were at par with S 2 (Sulphur @ 40 kg/ha). Similar results were recorded by Chattoo et al (2018) [14] , Choudhary et al (2018) [15] in garlic, Hariyappa (2003) [18] , Jaggi (2005) [19] , Singh et al (2019) [25] and Raghavendra et al (2020) [22] in onion, respectively.…”
Section: Effect Of Sulphur 1 Growth Attributessupporting
confidence: 82%
“…Results are in agreement with Balemi, 2005 who found an increase in TSS% in onion tissues when used 75% from recommended nitrogen per hectare with using Azotobacter bacteria as biofertilizer. Also, Singh et al, 2017 found that the treatment (50%N + 75%P + K + 50% Azotobacter + 25% PSB) enhanced the TSS% in onion tissues to 12.28%. Same findings also reported by Yaso et al, 2007;Abo-Sedera et al, 2012;Fawzy et al, 2012 andGhodia, 2012.…”
Section: Total Soluble Solids (Tss%)mentioning
confidence: 87%